Descriptions of Two Digenean Trematodes Found from a Chinese Sea Snake, Laticauda semifasciata, in Republic of Korea - Choe, Seongjun; Kim, Il-Hun; Kim, Min-Seop; Lee, Hae Rim; Kim, Youngjun; Eom, Keeseon S. (Korean journal of parasitology, 2020)
We intended to describe 2 digenean trematodes found from a Chinese sea snake, Laticauda semifasciata, as the new fauna in the Republic of Korea. The snake was caught offshore of Aewol-eup, Jeju-do, in August 2017. Two species of fluke were found in the lung and intestinal tract of the snake in the process of necropsy. They were identified as Pulmovermis cyanovitellosus Coil and Kuntz, 1960 and Harmotrema laticaudae Yamaguti, 1933, respectively based on the morphological characters. Pulmovermis cyanovitellosus showed elongated body with well-developed and elongated male genital system and compact vitelline. And H. laticaudae was characterized by linguiform body with heavily armed cirrus with excretory system. This is the first time both species have been reported and described off the Korean coast. We provide morphological descriptions with some comments on their biology and geographical distribution. In addition, the taxonomic validity of the genus Hydrophitrema Sandars, 1960 was discussed, in terms of morphological descriptions and host ranges. This study provides novel insight into digenean fluke species existing off the coast of Korea.